2020
DOI: 10.1093/mnras/staa3188
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic scale of star formation – I. Clump formation efficiency on local scales

Abstract: We have used the ratio of column densities (CDR) derived independently from the 850-mum continuum JCMT Plane Survey (JPS) and the 13CO/C18O (J = 3 → 2) Heterodyne Inner Milky Way Plane Survey (CHIMPS) to produce maps of the dense-gas mass fraction (DGMF) in two slices of the Galactic Plane centred at ℓ = 30○ and ℓ = 40○. The observed DGMF is a metric for the instantaneous clump-formation efficiency (CFE) in the molecular gas. We split the two fields into velocity components corresponding to the spiral arms tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…There are also a number of papers that have estimated core or clump formation efficiency in different environments, and comparing our results with them can gain more useful information about the physical properties of the parent molecular clouds. Recent studies have suggested that the average CFE on Galactic scales is about 8% (Eden et al 2012;Battisti & Heyer 2014;Eden et al 2021), consistent with the low efficiency found in simulation (Padoan & Nordlund 2002). According to the calculation of Nguyen Luong et al ( 2011), the clumps formation efficiency of the whole W43 molecular complex is about 11%.…”
Section: Properties and Formation Of Cores In Afgl 333-ridgesupporting
confidence: 67%
“…There are also a number of papers that have estimated core or clump formation efficiency in different environments, and comparing our results with them can gain more useful information about the physical properties of the parent molecular clouds. Recent studies have suggested that the average CFE on Galactic scales is about 8% (Eden et al 2012;Battisti & Heyer 2014;Eden et al 2021), consistent with the low efficiency found in simulation (Padoan & Nordlund 2002). According to the calculation of Nguyen Luong et al ( 2011), the clumps formation efficiency of the whole W43 molecular complex is about 11%.…”
Section: Properties and Formation Of Cores In Afgl 333-ridgesupporting
confidence: 67%
“…Kalberla & Haud (2019) investigated the turbulent properties of HI separated into the CNM, LNM, and WNM to reveal that each phase has distinct turbulent properties. Eden et al (2021) analysed the two-dimensional spatial power spectrum (SPS) of maps of the dense gas mass fraction derived independently from a combination of H 2 column density estimated from dust continuum and the ratio of CO intensities to show ∼10 pc is the characteristic scale for the largest variations in the clump and star formation efficiencies in CO-traced clouds formed by supersonic turbulence. Pingel et al (2018) explicitly compared the turbulent properties of several multi-wavelength tracers in the Perseus molecular cloud including dust, HI, and CO. Each tracer showed characteristics of a distinct turbulent environment, such as self-gravitating, supersonic medium in the dust and mostly transonic medium in the HI.…”
Section: Introductionmentioning
confidence: 99%
“…Kalberla & Haud (2019) investigated the turbulent properties of H i separated into the CNM, LNM, and WNM to reveal that each phase has distinct turbulent properties. Eden et al (2021) analyzed the two-dimensional spatial power-spectrum of maps of the dense gas mass fraction derived independently from a combination of H 2 column density estimated from dust continuum and the ratio of CO intensities to show ∼10 pc is the characteristic scale for the largest variations in the clump and star formation efficiencies in CO-traced clouds formed by supersonic turbulence. Pingel et al (2018) explicitly compared the turbulent properties of several multi-wavelength tracers in the Perseus molecular cloud including dust, H i, and CO. Each tracer showed characteristics of a distinct turbulent environment, such as self-gravitating, supersonic medium in the dust and mostly transonic medium in the H i.…”
Section: Introductionmentioning
confidence: 99%